Metode Mind Mapping Meningkatkan Keterampilan Menulis Karangan Narasi - Krisnawati, I Gusti Ayu; Budiarsa, Made; Seri Malini, Ni Nyoman Luh (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 23 (2016): September 2016)
This study aimed at finding out the writing skill of narrative text in tenth grade students of SMA 1 Sukawatibefore and aftter the application of Mind mapping. The sampling were purposely taken from class X.7 consisting of 37 students and class X.10 consisting of 36 students. This study was designed in the form of quasi experiment with nonequivalent control group design. This study consists of two stages, pretest was used to obtain the data before treatment and posttest to obtain data after treatment and applied themind mapping method. To collect data, four instruments were used; test, observation, questionnaires and documentations. The result of analysis was presented in the table, chart, and also in descriptive explanation. The result of analysis showed that students who obtained  treatment with the mind mapping method achieved higher  score than the students who didn’t obtain treatment. During  posttest, the control group students achieved score 74,91 while the experimental group students achieved  score 79,08.
Keywords: writing, narrative text, mind mapping